An Econometric Study of the Determinants of Foreign Direct Investment in Sudan During the Period (1999 – 2019) by using the Autoregressive Distributed Lag Model (ARDL) - Osman, Hassan Ali; Hassan, Ezaldeen Abdulrahman; Abkar, Abdelgalal Osman Idris (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed at measuring the impact of determinants of foreign direct investment in Sudan during the period (1999 – 2019). The study problem lies in the main question: Why wasn’t the foreign investment in Sudan at the required level, despite the availability of investment prospects and obstacles-free environment that was supposed to attract investors? The descriptive analytical method was used in the theoretical part of the study, while the statistical method based on econometrics tools analysis, (ARDL) was used in the practical part. The study’s data was collected from the Central Bureau of Statistics and Central Bank of the Sudan. The most important hypothesis the study assumed that, there was a reverse relationship between inflation and direct investment in Sudan. The study concluded that, there is a negative relationship between inflation and foreign direct investment in Sudan. It also concluded that, there is a negative relationship between inflation and foreign direct investment in Sudan. Moreover, the study reached that, the exchange rate and financing cost on foreign direct investment equal % 70. This means that the independent variables have 70% effect on the dependent variable. The study recommended that, financial and monetary authorities have to maintain economic stability, curb inflation, set a fixed exchange rate and reduce the economy’s financing cost.